1996
DOI: 10.1117/12.258972
|View full text |Cite
|
Sign up to set email alerts
|

<title>Large off-resonance nonlinear index changes at 1310 nm and 1545 nm observed in ytterbium-doped fiber</title>

Abstract: The resonant nonlinearity observed in rare-earth doped fibre is of interest for all-optical switching due to the very low pump powers needed to achieve complete switching. Large nonlinear effects have been observed previously in both erbium and neodymium doped fibres, however, these large effects cannot be explained by taking into account the change in absorption of local transitions alone.Two mechanisms have been suggested to account for these anomalously large index changes, namely thermally induced effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A pertinent issue that arises is the role of the periodic corrugation which has been shown to couple light into a range of longitudinal propagation angles through diffraction [Åslund et al 2005, 2006]. In recent work, it was reported that the degradation after 35 m of fibre retains the original Gaussian profile of the launch beam but has spread [Aslund & Canning 2009] -figure 6. This suggests that degradation of air-clad fibres are likely to be dominated by modal diffusion arising from coupling into many modes by scattering from the corrugated inner surface of the air, similar to the micro bending often cited as the origin of modal diffusion when interpreting high NA multimode polymer clad fibres for astronomy [Gloge 1972].…”
Section: Large Mode Areasmentioning
confidence: 98%
“…A pertinent issue that arises is the role of the periodic corrugation which has been shown to couple light into a range of longitudinal propagation angles through diffraction [Åslund et al 2005, 2006]. In recent work, it was reported that the degradation after 35 m of fibre retains the original Gaussian profile of the launch beam but has spread [Aslund & Canning 2009] -figure 6. This suggests that degradation of air-clad fibres are likely to be dominated by modal diffusion arising from coupling into many modes by scattering from the corrugated inner surface of the air, similar to the micro bending often cited as the origin of modal diffusion when interpreting high NA multimode polymer clad fibres for astronomy [Gloge 1972].…”
Section: Large Mode Areasmentioning
confidence: 98%